Intergenerational Transmission of Preferences and Parental Behaviours - Flavia Coda Moscarola; Daniela Del Boca; Giovanna Paladino (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper investigates the intergenerational transmission of preferences between parents and their children, examining the transmission of patience, propensity to save, and conscientiousness. We explore the role of specific parental behaviours, such as sharing financial information, in this transmission process. Using data from a representative survey of Italian households (parents with children 14-20 years of age) our analysis reveals a significant and positive correspondence between parents' and children's preferences. The results indicate that sharing information strengthens the transmission of patience between parents and children, particularly among children under 18, households with a socioeconomic status (SES) above the median, and daughters. Conversely, sharing information does not impact significantly the transmission of the propensity to save or conscientiousness.
Keywords: D14; I21; J24; 330; intergenerational transmission; patience; propensity to save; conscientiousness; parental behaviours